Transfer of beef bacterial communities onto food-contact surfaces - Guron, Giselle K. P.; Cassidy, Jennifer M.; Chen, Chin-Yi; Paoli, George C. (Frontiers in Microbiology, 2024)
Food spoilage and pathogenic bacteria on food-contact surfaces, especially biofilm-forming strains, can transfer to meats during processing. The objectives of this study were to survey the bacterial communities of beef cuts that transfer onto two commonly used food-contact surfaces, stainless steel (SS) and high-density polyethylene (HDPE) and identify potentially biofilm-forming strains. Top round, flank, chuck, and ground beef were purchased from 3 retail stores. SS and HDPE coupons (approximately 2cm × 5cm) were placed on beef portions (3h, 10°C), after which, the coupons were submerged halfway in PBS (24h, 10°C). Bacteria from the beef cuts and coupon surfaces (n=3) were collected, plated on tryptic soy agar plates and incubated (5 days, 25°C). Beef and coupon samples were collected for bacterial community analysis by 16S rRNA gene amplicon sequencing. In addition, bacteria isolated from beef and coupon samples from one store were identified by 16S rRNA gene amplicon sequencing and all isolates were assayed for biofilm formation using a crystal violet binding (CV) assay (72h, 10°C). Sixty-one of 972 beef isolates, 29 of 204 HDPE isolates, and 30 of 211 SS isolates were strong biofilm-formers (Absorbance>1.000 at 590 nm in the CV assay). Strong-binding isolates identified from one of the stores were of the genera Pseudomonas, Acinetobacter, Psychrobacter, Carnobacterium, and Brochothrix. Coupon bacterial communities among stores and cuts were distinct (p<0.001, PERMANOVA), but there was no distinction between the communities found on HDPE or SS coupons (p>0.050, PERMANOVA). The bacterial communities identified on the coupons may help determine the communities capable of transferring and colonizing onto surfaces, which can subsequently cross-contaminate foods.